ANALYSIS IMPLEMENTASI PROGRAM PEMBERDAYAAN EKONOMI MASYARAKAT PESISIR DI KABUPATEN PANGKEP - Achmad Rizal (AgriSains, 2015)
The objective of this research was to study how components of the Coastal Community Economic Development Program implemented in Pangkep Regency could improve the welfare of fishermen. This research used a linear multiple regression method. Research results showed that  the community economic welfare in Pangkep Regency was simultaneously influenced by revolving fund, productive economic fund, cooperatives, public consultation (socialization), technical and managerial training. Partially, revolving fund was the most significant variable. Training variable was the least significant due to various factor namely the heterogeneity of education level among the community as well the lack of understanding in absorbing the Coastal Economic Development Program message. Key Words: Behavior, coastal community, income.